Neutrality: a cornerstone of facilitation practice? - Boesten, Ida (2021)
There is a growing need for sustainability transitions in the world. Inclusive environmental governance could be a tool to enable these and is therefore getting increasingly popular. The use of stakeholder and citizen dialogues is recognized to be fundamental to strategies for inclusive environmental governance. Here, facilitators come in to elicit equitable and effective dialogues through structuring diverging interests and thoughts together with the participants. Facilitators hold a special place in the process and several scholars identified tensions that the facilitator consequently faces within the practice. To enable the desired dialogue, they must be able to switch smoothly between different roles; On the one hand, the responsibility for a fair process and, on the other hand, ensuring that the values of the participants are sufficiently acknowledged in the dialogue. There is a common understanding about that a facilitator should be neutral, while at the same time actively making sure that all parties get to have a voice in the process. This causes for tensions in the identities of the facilitators. The potential of facilitation is in the effective representation of resource users’ interests in the deliberative process which in turn can contribute to more equitable decisions on resource allocation, access and management rights. Though, the confusion about neutrality tends to make it more difficult to fulfil this potential.